Student Critical Self-Reflection and Perceptions of Video-Based Pro-Section Computer-Assisted Instruction - Emily S. Ho; Erica Dove; Lorna Aitkens; Andrea Duncan; Anne M. R. Agur (Journal of Medical Education and Curricular Development)
Introduction The cost, high resource demands, and psychological significance of in-person cadaveric labs are barriers to their use. Computer-assisted instruction (CAI) of gross anatomy is widely available as an alternative option. However, student engagement, reflections, and expectations of learning anatomy with CAI instead of in-person labs may influence their learning experience and outcomes. Purpose To evaluate students’ critical self-reflection and perceptions of learning using online self-guided anatomy modules with video-based pro-section CAI. Methods A prospective observational cross-sectional study was conducted with first-year occupational therapy students who received anatomy education using CAI involving online self-guided anatomy modules with video-based pro-section instruction. Critical self-reflection was measured using Kember's Critical Self-Reflection Questionnaire scores and open-ended comments. Paired analysis of self-reported Kember nonreflective and reflective actions was conducted followed by quantitative (correlation, Student t -tests) and qualitative (directed content analysis) exploration of factors associated with critical self-reflection. Results Of the 126 students enrolled in the study, 97 consented and completed the study. The students’ Kember Understanding (U) subscale mean score was significantly higher than the Habitual Action (HA), Reflection, and Critical Self-Reflection subscales. The largest effect size was found between the U and HA subscales ( d s  = 1.3, 95% CI [1.0, 1.5]). Academic outcomes (anatomy quiz sum score, term grade) did not correlate with the Kember scores. Overall, students felt that video-based anatomy pro-section CAI was best used in a supplementary manner and opportunities for hands-on learning of anatomy were needed. Conclusion Video-based anatomy pro-section CAI helped students understand anatomy but did not readily engage students in critical self-reflection. Strategic course and curriculum design with integrated and hands-on learning opportunities are needed to optimize student anatomy learning experience and academic outcomes while using this type of CAI.